2011
DOI: 10.5665/sleep.1170
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and Daytime Sleepiness Are Risk Factors for Depressive Symptoms in the Elderly

Abstract: Insomnia symptoms, EDS, and the use of medication independently increase the risk of subsequent depression in the elderly. In clinical practice, disturbed sleep and prolonged use of sleep medication may be early indicators or potentially reversible risk factors for depression, suggesting the need for further clinical interventional research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
118
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(142 citation statements)
references
References 31 publications
23
118
1
Order By: Relevance
“…With regard to depression, the literature suggests that clinical depression is a predictor of cardiovascular disease among women 64 and is associated with sleep disturbances. 65 In this study, among women with a high insomnia level (WHIIRS ‡ 9), 20.8% were depressed compared with only 6.6% of those with a WHIIRS < 9 ( p < 0.001), and it is likely that these differences in depression status may impact sleep characteristics. Although we adjusted for depression using the [CESD/DIS] measure, the Burnam screen is not a perfect measure of clinically diagnosed depression.…”
Section: Discussionmentioning
confidence: 94%
“…With regard to depression, the literature suggests that clinical depression is a predictor of cardiovascular disease among women 64 and is associated with sleep disturbances. 65 In this study, among women with a high insomnia level (WHIIRS ‡ 9), 20.8% were depressed compared with only 6.6% of those with a WHIIRS < 9 ( p < 0.001), and it is likely that these differences in depression status may impact sleep characteristics. Although we adjusted for depression using the [CESD/DIS] measure, the Burnam screen is not a perfect measure of clinically diagnosed depression.…”
Section: Discussionmentioning
confidence: 94%
“…Jaussent et al [38] reported that insomnia symptoms independently increased the risk of subsequent depression. The design used in the present study did not support the categorization of psychiatric disorders as either a risk factor or a consequence of the disorder, such as in longitudinal cohort studies.…”
Section: Discussionmentioning
confidence: 98%
“…Physiological levels of melatonin influence sleep quality and circadian biological rhythmicity, and poor sleep quality and circadian misalignment are associated with metabolic abnormalities and depressed mood (14,34,35). Low physiological levels of melatonin are also associated with increased incidence of diabetes and hypertension (36,37).…”
Section: Discussionmentioning
confidence: 98%